Komunikasi dalam Menjaga Hubungan Pernikahan Jarak Jauh: Istri Bekerja sebagai TKW - Ilham Kurniawan; Meita Dwi Mukhlishotul Azizah; Muhammad Rafli Rasidin; Andhita Risko Faristiana (Lembaga Pengembangan Kinerja Dosen, 2023)
A shift in the role of living by the head of the family or a husband is replaced by a wife who works as a Women's Working Power (TKW) abroad. It's already happening because of the demands of the family economy. That decision affects the relationship and distance communication of the couple. Although the progress of communication technology is so rapid as the media is the point of the problem is to manage communication and relationships to stay harmonious. The research study was conducted out at the Bulugunung village, district of Plaosan, Magetan. The research methodology used is field research applying qualitative research methods. Qualitative methods produce descriptive data with data collection techniques such as observations and interviews. The results that follow are the study’s conclusion. (1) The condition of couples with long-distance marriages in communicating, (2) the way the couples take advantage of the supporting and hindering factors of distance communication, and (3) the distance interpersonal communication patterns between spouses inining distance marital relationships. Collaboration and mutual trust are the key to the harmony of relationships and communication of distant married couples.